Prevalence of metabolic syndrome in a rural area of Brazil - Velásquez-Meléndez, Gustavo; Gazzinelli, Andrea; Côrrea-Oliveira, Rodrigo; Pimenta, Adriano Marçal; Kac, Gilberto (São Paulo Medical Journal, 2007)
CONTEXT AND OBJECTIVE: Metabolic syndrome (MS) is recognized worldwide as an important public health concern. However, little information is available for rural populations in Brazil. The aim was to determine the prevalence and risk factors associated with MS in a rural village in Brazil in 2004. DESIGN AND SETTING: Cross-sectional population-based study, in Virgem das Graças, a rural community in the Jequitinhonha Valley, State of Minas Gerais. METHODS: MS was the dependent variable, defined as any three of these risk factors: arterial hypertension, high glucose or triglyceride concentrations, low high-density lipoprotein cholesterol and abdominal obesity. MS prevalence, according to selected socioeconomic and demographic variables (age, skin color, marital status, schooling and smoking habits), was determined in 251 subjects aged 20-88 years. Multivariate logistic regression was used to estimate odds ratios (OR) and 95% confidence intervals. RESULTS: MS prevalence was 21.6% (7.7% for men and 33.6% for women); the age-adjusted prevalence was 19.0%. The highest prevalences were observed for women > 60 years of age (52.9%) and women with body mass index (BMI) ≥ 25 kg/m2 (64%). Age, sex and BMI were associated risk factors for MS, while skin color was only significantly associated with MS for women. The models were adjusted for age, smoking habits, marital status, skin color and schooling. CONCLUSIONS: BMI and age were independently associated factors for MS in this rural community. These findings provide important evidence on the prevalence of MS as a public health problem, particularly for women and overweight individuals.